Analisis Pemahaman Masyarakat Terhadap Akad Bank Syariah di Desa Mandalaguna Kecamatan Salopa Kabupaten Tasikmalaya - Salman Al Farizi; Adun Rahman; Yusup Ansori; Muhammad Romli; Adi Susandi (BISMA : Business and Management Journal, 2026)
This study aims to analyze the level of public understanding of Islamic banking contracts (akad), identify public perceptions of Islamic banking, and examine the factors influencing such understanding in Mandalaguna Village, Salopa District, Tasikmalaya Regency. The study employed a qualitative approach using a field research design. Data were collected through observation, semi-structured interviews, documentation, and questionnaires administered to participants selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing and verification. The findings reveal that the community's understanding of Islamic banking contracts remains relatively low. Although most respondents recognize that Islamic banks operate based on Islamic principles and prohibit riba (interest), they lack a comprehensive understanding of contracts such as mudharabah, murabahah, musyarakah, and wadiah. The community generally holds positive perceptions of Islamic banking; however, the decision to use Islamic banking services is still influenced by accessibility, familiarity with conventional banks, and limited information regarding Islamic banking products. The low level of Islamic financial literacy is primarily attributed to inadequate public education, the complexity of Arabic contract terminology, limited access to information, and differences in educational background. This study recommends strengthening Islamic financial literacy programs through collaboration among Islamic banking institutions, government agencies, educational institutions, and community leaders.